The actual conditions of traditional Japanese Kampo education in all the pharmacy schools in Japan: a questionnaire survey after the enforcement of the new national 2015 core curriculum - Yoshinobu Nakada; Makoto Arai (BMC, 2018)
Abstract Background To investigate the present status of Kampo education, which has still not been elucidated, after the introduction of the new core national curriculum of 2015 into nationwide pharmacy education, in all 74 pharmacy schools in Japan. Methods A postal questionnaire survey was conducted from August 2015 to January 2016. The completed questionnaires were returned by mail. Web-based syllabi were also investigated to ascertain the detailed lecture curricula in each school. Descriptive analyses were conducted without statistics. Results A total of 74 questionnaires were collected (response rate, 100%). In 2015, the numbers of clinical Kampo classes as required subjects during the 6 years of regular pharmacy school education ranged from 0 to 36 (median, 13; mean, 11.8 ± 7.6). Of the 74 schools, 49 schools (66%) provided Kampo education from a clinical standpoint. Pharmacists employed in pharmacies and physicians taught most of these classes. The major problems to be solved first are: selecting and retaining teachers to teach clinical Kampo medicine (43 of 74 schools, 58%), preparing standard textbooks (37 schools, 50%), and improving the environment for practical Kampo training (30 schools, 41%). Conclusions Curricula for teaching Kampo medicine significantly differ at each of the 74 Japanese pharmacy schools. In addition to selecting teachers who can adequately teach clinical Kampo medicine, improving training environments, and nationwide standardization of the curricula and textbooks are critical.